(untitled) (Revista Española de Fisiología, 1971)
Comparative studies have been made of the renewal velocity of plasmatic iron in laying and non-laying hens, using radioactive techniques. It can be observed that the disappearance of iron from the plasma has properties common to both groups. Nevertheless, the renewal velocity is much greater with laying hens which can be explained by an additional demand of iron for egg formation.